(untitled) (Aporte Santiaguino, 2019)
The purpose of this work was to identify the insects associated with aguaymanto in the location of Cerro Punta. For this, three random samplings were carried out, choosing seven plants per sampling, from which photographs were taken and specimens were collected, for later identification and diagnosis. According to the results, respect to the phytophages, Antianthe expansa(Membracidae)was the most abundant species, followed by Oncopeltus sp. (Lygaeidae), Euschistus heros (Pentatomidae) and Epitrix sp. (Chrysomelidae). In case of predators, Zelus longipes, Z. renardii (Reduviidae) and Polybia sp. (Vespidae) were important; whereas in parasitoids, Enicospilus sp. (Ichneumonidae) and Pompilidae wasps were the most frequent. Apis mellifera (Apidae), was the main pollinator species, found in all plants and in all samples. In conclusion, there are at least 38 taxa associated with golden berry in Cerro Punta, from which 45 % are phytophagous, 18 % predators, 24 % parasitoids, 8 % pollinators, 2 % detritivores and 3 % saprophytes. Although Antianthe expansa is an important pest of peppers and was the most abundant insect observed during the study, the beneficial species found represent a potential to be explored, as an integrated management strategy in the agroecosystem.